Distribución de cangrejos ermitaños (Anomura: Paguroidea) en el mar Caribe colombiano. - Martínez Campos, Bibian (2012)
Hermit crabs represent the marine life in the Colombian Caribbean, and are important for the dynamic equilibrium maintenance in ecosystems, the ecological interactions and their impact on food web stability. Generally, in order to come up with some conservation strategies, strong bio-geographical information is needed for policies definition. With this aim, this study analyzed the distribution patterns of hermit crabs in the Colombian Caribbean Sea, through classification and spatial ordination multivariate analyses, using historical records from years 1916 to 2006. Besides, the world distribution of Colombian species and their geographic affinity in the Caribbean and Western Atlantic were identified. The results show deep differences between coastal and continental slope faunas, and latitudinal differences in the assemblages, with the identification of three groups: Northeast, Center and Southwest. The differences in faunal composition that support these three groups were determined. Based on maps of the Colombian marine ecosystems, it was found that the main factors affecting the distribution of hermit crabs were the Caribaná slope (depth), water-mass temperature, Guajira sea-grass beds, and particular conditions of ?Coralline Archipelagos? and ?Darién? eco-regions. Colombian hermit crab fauna is more related to the North Atlantic and the Antilles, than to the South Atlantic and the Gulf of Mexico. Additionally, geographical sub-provinces in which Colombia is included, these were found as transition zones among Northern and Austral subprovinces of the Greater Caribbean.